(untitled) (Papeles, 2022)
Introduction: The main objective of the reported study is to characterize the content of existing mathematical memes on the internet and in some social networks. The problem related to the evolution of the concept “meme” and its implications in education mediated by technology is addressed. Methodology: The research was based on a qualitative exploratory study where content analysis was implemented as a method to analyze memes and generate themes that evidenced the characteristics of the selected memes. Results and discussion: The research provides a characterization of the content of mathematical memes, we recognize that their content addresses situations of daily life, cartoon scenes, movies that invite students to analyze analogies of the situation presented with the symbolic expressions typical of mathematics. Conclusions: The memes allow to identifying the necessary knowledge to study mathematical concepts, formulas, derivatives, integrals to mention a few and evidences the use of the mathematical symbols in contexts of daily life.